Content and distribution of conjugated linoleic acid isomers in bovine milk, cheese and butter from Azores - Pestana, Jose M. (2015)
Pasture intake is a major factor affecting the content and the distribution of the conjugated linoleic acid (CLA) isomers in bovine milk fat. The aim of this study was to determine the CLA contents and its isomeric distribution in milk, cheese and butter